(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
A selective and new spectrophotometric method is described for determination of three antiepileptic drugs; namely lamotrigine (LAM), gabapentin (GAB), and oxcarbazepine (OXC) in drug substances and in drug products using vanillin reagent as the chromogenic agent. The method is based on a coupling reaction between the cited drugs and vanillin reagent in acidic condition. Under optimized conditions, the yellow colored products were measured at 405, 396, and 400 nm respectively. Beerâ€™s law was obeyed at (0.4 â€“ 10), (0.1-10), and (0.5-11) Î¼g/mL, andÂ the calculated molar absorptivity values are 2.52 x 104, 1.74 x 104, and 2.54 x 104 L/mol/cm for LAM, GAB, and OXC respectively. Sandell sensitivity, the limit of detection (LOD) and limit of quantification (LOQ) were calculated. No interference was observed from common additives found in drug products. The presented method was validated according to ICH guidelines. Statistical comparison of the results was performed using Student’sÂ t-test and F-ratio at 95% confidence level, and there was no significant difference between the reference and proposed method with regard to accuracy and precision. The method offers the advantages of rapidity, simplicity and sensitivity and low cost and can be easily applied to resource poor settings without the need for expensive instrumentation and reagents.